Teaching Hinduism to children with special needs: The experience of SLB N 2 Mataram - Meiniawati, Dewa Ayu (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2025)
Religious education plays an important role in forming children’s character and identity, including for children with special disabilities. This study aims to explore the implementation of Hindu religious education at SLB N 2 Mataram, focusing on the learning methods used, the challenges faced, and its impact on these children's spiritual and social development. Data were collected through interviews, observations, and documentation studies using a qualitative approach. The results of the study indicate that despite various challenges, Hindu religious education can provide a significant positive contribution to the development of children with special disabilities, both in spiritual and social aspects. These findings emphasise the importance of religious education as a tool to build self-confidence, empathy, and social connectedness for these children and provide new insights into the practice of inclusive education in a religious context.